Multiple myeloma-derived exosomes inhibit osteoblastic differentiation and improve IL-6 secretion of BMSCs from multiple myeloma. (28th November 2019) - Liu, Zhaoyun; Liu, Hui; Li, Yanqi; Shao, Qin; Chen, Jin; Song, Jia; Fu, Rong
Abstract : Bone marrow stromal cells (BMSCs) play a critical role in multiple myeloma (MM) pathogenesis by cell contact, and secretion of cytokines, growth factors and extracellular vesicles. Exosomes are secreted by almost all cell types and are recently reported to mediate local cell-to-cell cross-talk by transferring messenger RNAs, LncRNAs, and proteins. Compelling studies have identified BMSC-derived exosomes induce proliferation, migration, survival, and drug resistance of MM cells. However, whether MM cell-derived exosome also plays a role in function in BMSC remains unclear. Here we investigated the effect of MM cell-derived exosomes on the interleukin (IL)-6 secretion and osteoblastic differentiation capability of BMSC from patients with MM. Furthermore we investigated the IL-6 secretion relative regulation protein APE1 and NF-kB and osteoblastic differentiation protein Runx2 (runt-related gene 2), Osterix and osteocalcin (OCN). Our results showed that MM cell-derived exosomes promoted IL-6 secretion and suppressed osteoblastic differentiation and mineralization of BMSCs. Mechanistically, we demonstrated that MM cell-derived exosomes lead to an increase in APE1 and NF-kB and a reduction in Runx2, Osterix and OCN in BMSCs. Taken together, MM cell-derived exosomes induce the secretion of IL-6 and poor osteoblastic differentiation of BMSCs.